Efek Pelaksanaan Peraturan Pemerintah No 46 Tahun 2013 terhadap Efektifitas Penerimaan PPH Final bagi Wajib Pajak UMKM pada Kantor Pelayanan Pajak Pratama Makassar Selatan - Andi Syamsul Kahar (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2019)
Micro, Small and Medium Enterprises (MSMEs) are the largest group of economic actors in the Indonesian economy and have proven to be the safety valve of the national economy in times of crisis, as well as being a dynamic economic growth post-economic crisis. In addition to being the largest business sector contributing to national development, MSMEs also create considerable employment opportunities for domestic workers, so it greatly helps efforts to reduce unemployment. In the definition of small and medium enterprises that vary, there are at least two aspects, namely aspects of labor absorption and aspects of grouping companies in terms of the number of workers absorbed in the group / group of companies.The empirical facts in this study, especially for certain Gross Income Taxpayers (MSMEs), as stipulated in PP 46 of 2013, at the Pratama South Makassar KPP, have positive growth rates and contributions.Meanwhile, one of the impacts of PP-46/2013 is the new compulsory netting in realizing tax extensification in South Makassar KPP Pratama, one of the developments in the efforts to extend taxpayers in the MSME sector as stipulated in the PP-46 scheme.By looking at the level of development and growth as well as the contribution of PP-46 taxpayer SMEs in the South Makassar Pratama KPP mentioned above, in general MSMEs in the national economy have a role: (1) as the main actors in economic activity, (2) the largest provider of employment (3) important players in the development of the local economy and community empowerment, (4) the creator of new markets and sources of innovation, and (5) their contribution to the balance of payments. Therefore empowerment must be carried out in a structured and sustainable manner, with the direction of increasing productivity and competitiveness, as well as fostering powerful new entrepreneurs.